Constructivism, Embedded Liberalism and Anti-Dumping - Canadian Public Interest Inquiry as Case Study of Embedded Liberalism - Aoun, Wissam (2017)
The majority of proposals for international antidumping reform focus almost entirely on the relevant economic factors- consumer welfare losses and gains. Therefore, almost all proposals come to the exact same conclusion; in light of the enormous welfare losses suffered by domestic consumers, international antidumping law should be repealed in its entirety, or at least replaced by some form of international competition law. However, this analysis views the issue of antidumping law through the constructivist lens, and more specifically, the embedded liberalism view of international trade law. From this perspective, economics alone does not grasp the constitutive realities at play in antidumping law; domestic perspectives of legitimacy and fairness shape the contours of international antidumping law, and these constitutive norms espouse a view that protectionism, in a variety of different shapes and forms, is as much a part of international trade law as the traditional laissez-faire liberalist approach. This paper concludes that public interest inquiries, which form part of a small number of countries’ antidumping laws, embraces the constitutive realities at play in antidumping law and provide an opportunity for development of legitimate international antidumping reform. This paper examines the Canadian approach to public interest inquiry in antidumping, including recent developments. This paper concludes that the current Canadian experience demonstrates that embracing a public interest inquiry as part of antidumping reform may provide true hope for future development based on a embedded liberalism view of international trade relations.
Keywords: Wissam Aoun